2018
DOI: 10.5433/1679-0359.2018v39n3p983
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient accumulation in the shoots of physic nut grown in two edaphoclimatic conditions

Abstract: Abstract'The possibility of using physic nut oil as an alternative energy source indicates that it is necessary to carry out studies concerning the absorption and accumulation of nutrients in the distinct phases of development of the crop for the appropriate management of fertilizer application. Given this information, this study aimed to evaluate the accumulation of nutrients in the shoots of physic nut plants, as well as to identify critical nutrient uptake by this crop. The experiments were set up independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…The concentration of Ca in the fruit was very similar to that of K. This element must be available in sufficient quantity during the jatropha production phase (Magalhães et al, 2018). The Ca/Mg ratio in the present study indicates an Mg deficiency, and the Mg/K ratio indicates a deficiency of this element relative to K. According to Xu and Wang (2011), Mg plays a substantial role in P transport and oil and fat formation in the tree.…”
Section: Soil Characteristics and Effects Of Fertilizer Application Osupporting
confidence: 55%
See 2 more Smart Citations
“…The concentration of Ca in the fruit was very similar to that of K. This element must be available in sufficient quantity during the jatropha production phase (Magalhães et al, 2018). The Ca/Mg ratio in the present study indicates an Mg deficiency, and the Mg/K ratio indicates a deficiency of this element relative to K. According to Xu and Wang (2011), Mg plays a substantial role in P transport and oil and fat formation in the tree.…”
Section: Soil Characteristics and Effects Of Fertilizer Application Osupporting
confidence: 55%
“…Jatropha usually proliferated in the first two years after planting, and N is essential for the assimilation of carbon and the formation of new tree organs. According to Magalhães et al (2018) the maximum accumulation of nutrients in jatropha plants is reached at 2.8 years in leaves, stems, fruits, and shoots for N, P, and K, coinciding with the maximum accumulation of dry matter in the tree. Magalhães et al (2018) found that N accumulated in more significant proportions in the stem than in the leaves, while N levels in the leaves were subject to seasonal variations.…”
Section: Soil Characteristics and Effects Of Fertilizer Application Omentioning
confidence: 97%
See 1 more Smart Citation